Upper Limbs Trauma in Pediatrics - Piccolo, Claudia Lucia; Galluzzo, Michele; Trinci, Margherita; Ianniello, Stefania; Tonerini, Michele; Guglielmi, Giuseppe; Miele, Vittorio (Seminars in Musculoskeletal Radiology, 2017)
A correct interpretation of musculoskeletal imaging studies of children requires an in-depth knowledge of normal skeletal growth and physiologic changes in growing bones. During childhood the growing bones are more prone to acute and chronic injuries because of the imbalance between osseous structures and tendons and ligaments, so physeal injuries are the most commonly encountered types of lesions. This review addresses acute and chronic injuries involving the upper extremities in the pediatric population. These injuries may be subtle to recognize or atypical. The radiologist has to choose the most appropriate technique that can best recognize the problem and establish the correct diagnosis, thus avoiding diagnostic errors and potential delayed complications.
Keywords: children; musculoskeletal; physeal fractures; apophyseal fractures; chronic injuries